2012
DOI: 10.1016/j.ophtha.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Choroidal Thickness Measurements Across Three Spectral Domain Optical Coherence Tomography Systems

Abstract: Purpose To investigate the reproducibility of choroidal thickness measurements in normal subjects on three Spectral Domain Optical Coherence Tomography (SDOCT) instruments, Zeiss Cirrus HD-OCT (Carl Zeiss Meditec Inc, Dublin, California, USA), Heidelberg Spectralis (Heidelberg Engineering, Heidelberg, Germany) and Optovue RTVue (Optovue Inc., Fremont, CA). Design Cross-sectional non-interventional study Participants Images were obtained in 28 eyes of 28 healthy undilated volunteers without ocular pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(165 citation statements)
references
References 14 publications
5
153
1
6
Order By: Relevance
“…Previous studies also showed that the measurements of choroidal thickness, using EDI-OCT, have good reproducibility and repeatability. 25,26 Besides, considering the similarity of the normal values of this study and that of the previous studies, measuring error may not be significant. 10,26,27 In conclusion, increased SFCT of patients with CSC was reduced after spontaneous resolution and lowfluence PDT.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies also showed that the measurements of choroidal thickness, using EDI-OCT, have good reproducibility and repeatability. 25,26 Besides, considering the similarity of the normal values of this study and that of the previous studies, measuring error may not be significant. 10,26,27 In conclusion, increased SFCT of patients with CSC was reduced after spontaneous resolution and lowfluence PDT.…”
Section: Discussionsupporting
confidence: 60%
“…The thickness of the choroid at the areas 1500 mm nasal and 1500 mm temporal to the fovea was also examined (Figure 1). Two independent raters (MSD and YT) measured images without the information of the eye or other observer, as described previously 17 and the average of the two measurements was taken; the differences between readings of the masked physicians were found to be within 10% of the mean.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies excluded eyes with indistinct CSI or extrapolated the CSI. 18,19 Although exclusion of eyes with an indefinite boundary could result in higher repeatability, it might not reflect the practical aspects and cause selection bias. Hence, the current study adopted the extrapolation method, because the indistinct CSI should be considered a significant factor in measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous investigations revealed high reliability and a strong correlation when comparing repeatability after scanning with three different SD-OCT devices. 18,19 Yamashita et al, 18 however, only considered eyes for which a distinct choroid boundary was seen by both observers, and Branchini et al 19 also averaged the measurements of two observers. Consequently, their studies had a greater tendency to overestimate repeatability than ours.…”
Section: Eyementioning
confidence: 99%